Workshop Labeling Dan Packaging Untuk Meningkatkan Nilai Jual Produk Lokal Keripik Ketela Di Desa Semenpinggir Kecamatan Kapas Kabupaten Bojonegoro - Ifa Khoirianingrum; Sarjono Sarjono; Fruri Stevani; Ayis Crusma Fradani; Rika Pristian FA (IAI Darussalam, 2018)
The purpose of this community service program is to provide understanding to businesses about the importance of labels and packaging, provide training on good labels and packaging to business people and provide an understanding of how to increase the sale value of cassava chips. The method used in the community service program is to use the lecture method to provide an understanding of the management of small businesses, labels and appropriate tracking and label rules and regulations. Besides that, it uses a workshop method about design and packaging. The result of this community service program is that businesses know more about how to increase the selling value of products by labeling and packging. Key Words: Labels, Packaging, Local Chips Products